The Importance of Organizational Communication in Improving Employee Performance: A Case Study of the Regional Revenue Management Agency of the City of Bandung - Farida Yuliaty (International Journal of Science and Society, 2021)
This study aims to examine the effect of organizational communication on employee performance at the Bandung Regional Revenue Management Agency, both simultaneously and partially. This study uses explanatory surveys to analyze the influence between variables, both partially and simultaneously. Data collection was carried out by distributing questionnaires to 60 respondents who were sampled in the study. Data analysis and hypothesis testing in this study were carried out using path analysis. This research proves that organizational communication simultaneously and partially influences the performance of employees at the Bandung Regional Revenue Management Agency.